An Analysis of the Current Challenges of WEEE Remanufacturing. (2015) - Buşu, Alexandra Antonia; Muntean, Ionuţ; Stan, Sergiu-Dan
Abstract: As more strict requirements for environmental protection and resource utilization appear, a solution is represented by remanufacturing. Remanufacturing involves restoring and updating a used product to a like new condition and selling it with a warranty equal to that of a new product. It thus results in reduced manufacturing costs and lessens the amount of raw materials used. The paper presents a detailed description of the remanufacturing processes for waste electrical and electronic equipment (WEEE). The current challenges that a remanufacturer is faced with during the six stages of the process are also presented together with the solutions proposed in the literature to overcome these drawbacks.